The laws protecting pets in Poland - Bednarczyk, Małgorzata (Management and Administration Journal, 2019)
The paper tackles the issue of regulations protecting pets in Poland. The paper presents the development and current status of legislation in this area. The aim of this paper is to analyse the regulations and the available literature and analysis of the activities of state authorities in the supervision of animal protection laws.